PROYEKSI MINAT BELI KONSUMEN HIDROPONIK: Studi Pada CV. Hidro Sinergi Utama - Batubara, Maryam; Saputri, Yuliana (LP2M Institut Teknologi dan Bisnis Asia Malang, 2023)
This research aims to find the most significant selling potential of hydroponic plants. This study compared three types of hydroponic plants: kale, spinach and Pak Choy. The potential sales of the three plants were compared using several methods, namely Naive, Moving Average, Single Exponential Smoothing, and Decomposition Additive. Water spinach and Pak Choy got the highest forecast using the decomposition-additive sales forecasting method, while spinach used single exponential smoothing. The prediction of hydroponic and Pak Choy vegetable sales time is more varied than spinach, which is estimated to be the same as the previous year's sales. Water spinach and Pak Choy hydroponic vegetables have great sales opportunities in 2022.